2020
DOI: 10.1002/er.5078
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐analytical solution for time‐varying latent heat thermal energy storage problems

Abstract: Summary Latent heat thermal energy storage (LHTES) problems include a lot of boundary conditions that could not be solved by exact solution, so new approaches to solving such problems could revolutionize the advanced energy storage devices. This paper focuses on reformulating the generalized differential quadrature method (GDQM) for a one‐dimensional solidification/melting Stefan problem as a fundamental LHTES problem and solves some practical cases. Convergence and comparisons demonstrate that the proposed ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the previous article, 37 we introduced this method for phase change problems only in one phase. Then in another article, 36 we used it practically and evaluated various materials that can be used as PCM in thermal management systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous article, 37 we introduced this method for phase change problems only in one phase. Then in another article, 36 we used it practically and evaluated various materials that can be used as PCM in thermal management systems.…”
Section: Discussionmentioning
confidence: 99%
“…In other articles, 36,37 the authors of this article solved the Stefan problem, which deals with the problem of phase change as one region, using this method (GDQ). The results showed that using this method to solve the issues of phase change material (PCM) can quickly and accurately predict these materials' behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Guo et al 26 experimentally evaluated the performance of TES, which consists of fin and PCM with metal foam combinations. Some research papers developed analytical techniques to analyze the TES system 27,28 . On the other hand, research related to PCM implementation in building envelopes is investigated by Ji et al 29 Besides, Asker et al 30 computed energetic performance and CO 2 emission for building‐wall integrated with PCM using actual weather data for Izmir city.…”
Section: Introductionmentioning
confidence: 99%
“…Some research papers developed analytical techniques to analyze the TES system. 27,28 On the other hand, research related to PCM implementation in building envelopes is investigated by Ji et al 29 Besides, Asker et al 30 computed energetic performance and CO 2 emission for building-wall integrated with PCM using actual weather data for Izmir city. Some research focused on the use of TES in electric vehicles.…”
mentioning
confidence: 99%
“…It is a more energy‐efficient method than conventional accumulation 8 . The utilization of the PCM has been found to be useful for different applications including thermal management in building, 9‐11 performance enhancement in solar collectors, 12,13 and thermal energy storage 14,15 . There is an increasing research interest in using nanoparticles and fins for enhancing the thermal performance of the heat storage units 16‐19 …”
Section: Introductionmentioning
confidence: 99%